2014
DOI: 10.1093/molbev/msu251
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Origin and Diversification of Epidermal Barrier Proteins in Amniotes

Abstract: The evolution of amniotes has involved major molecular innovations in the epidermis. In particular, distinct structural proteins that undergo covalent cross-linking during cornification of keratinocytes facilitate the formation of mechanically resilient superficial cell layers and help to limit water loss to the environment. Special modes of cornification generate amniote-specific skin appendages such as claws, feathers, and hair. In mammals, many protein substrates of cornification are encoded by a cluster of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
331
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 116 publications
(346 citation statements)
references
References 50 publications
13
331
1
1
Order By: Relevance
“…The presence of an S100 domain strongly suggests that SFTPs have evolved from an ancestral S100A gene. [1] As the central domains of SFTPs contain sequence repeats and short sequence motifs similar to those present in proteins encoded by other EDC-encoded proteins such as loricrin, [15,25] an origin of the primordial SFTP by "fusion" of different types of pre-existing EDC genes has been hypothesized. However, the absence of EDC genes other than S100As and SFTPs in frogs, which represent phylogenetically basal tetrapods, is more compatible with the alternative hypothesis that SFTPs have originated before other EDC genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of an S100 domain strongly suggests that SFTPs have evolved from an ancestral S100A gene. [1] As the central domains of SFTPs contain sequence repeats and short sequence motifs similar to those present in proteins encoded by other EDC-encoded proteins such as loricrin, [15,25] an origin of the primordial SFTP by "fusion" of different types of pre-existing EDC genes has been hypothesized. However, the absence of EDC genes other than S100As and SFTPs in frogs, which represent phylogenetically basal tetrapods, is more compatible with the alternative hypothesis that SFTPs have originated before other EDC genes.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Our recent studies have suggested that SFTPs originated prior to the diversification of amniotes (mammals, reptiles and birds). [14][15][16] However, the evolutionary origin of SFTPs has remained uncertain because of incomplete genome data of the next relatives of amniotes, the amphibians. Here, we performed a comparative genomics study to infer the time of origin of SFTPs and to estimate when sequence elements of SFTPs, such as the carboxy-terminal motif implicated in binding keratin filaments, [14,17] have evolved.…”
Section: Questions Addressedmentioning
confidence: 99%
“…Keratins are also discussed in terms of mammalian keratin, reptilian keratin and avian keratin. Besides, studies on keratinization in vertebrates and the evolution of epidermal proteins have considered keratins as true keratin (a-keratin) and corneous beta-proteins (b-keratins) [33,34]. .…”
Section: Classification Of Keratinmentioning
confidence: 99%
“…Different from the KAPs present in the other vertebrates, keratin-associated beta-proteins form themselves filaments and likely also interfilamentous matrix material (Brush 1983;Fraser and Parry 1996, 2011. These proteins and their genes are however unrelated to keratins of the intermediate filaments, and no phylogenetic study conducted so far has shown a molecular relationship between the two types Strasser et al 2014).…”
Section: Beta-keratins Are Sauropsid Corneous Beta-proteinsmentioning
confidence: 99%
“…Therefore, all vertebrates, pisciform and terrestrial, produce filamentous keratins as a basic cytoskeletal framework to which KAPs or other corneous proteins (CPs) are later deposited as matrix material. It is believed that keratins of intermediate filaments originated before other corneous proteins and that the latter evolved later when the stratum corneum and different skin appendages evolved in relation to the formation of an EDC (Eckhart et al 2013;Strasser et al 2014). In sauropsids, among the other corneous proteins originated to form a stratum corneum, some possessed a betasheet region and were capable to form filaments (betakeratins) and not an amorphous matrix like other proteins.…”
mentioning
confidence: 99%